Re-description of the Arctic tardigrade Tenuibiotus voronkovi (Tumanov, 2007 (Eutardigrada; Macrobiotidea), with the first molecular data for the genus - Zawierucha, Krzysztof; Kolicka, Małgorzata; Kaczmarek, Łukasz (Zootaxa, 2016)
Tardigrada is phylum of micrometazoans widely distributed throughout the world, because of old descriptions and insufficient morphometric data, many species currently need revision and re-description. Tenuibiotus voronkovi (Tumanov, 2007) is tardigrade previously only recorded from the Svalbard archipelago. This species’ original description was based on two individuals with destroyed claws on the fourth pair of legs and a lack of complete morphometric data for buccal tube and claws. In this paper, we present a re-description of T. voronkovi, supplementing the original description using the original paratype and additional material from Svalbard: Spitsbergen, Nordaustlandet and Edgeøya. This species is characterised by two macroplacoids and a microplacoid, claws of Tenuibiotus type, dentate lunules under claw IV, and faint granulation on legs I–III and strong granulation on the legs IV. We include a new morphological description with microphotographs, morphometric, and molecular data (including: mitochondrial cytochrome c oxidase subunit I (COI), internal transcribed spacers (ITS1–5.8S rDNA–ITS2), and nuclear ribosome subunits 28S rRNA and 18S rRNA). These are the first published molecular data for the genus Tenuibiotus Pilato and Lisi, 2011, analysis of which indicated an affiliation of Tenuibiotus to the family Macrobiotidae. We found no differences in body size between individuals from different islands (Nordaustlandet and Edgeøya), but did observe variability in the eggs. After revision of the literature and the published figures, we concluded that Dastych’s (1985) report of T. willardi (Pilato, 1976) from Svalbard, was actually T. voronkovi, which has the greater distribution in Svalbard, and other Arctic locations, than previously believed.